Determination of ternary mixtures of vitamins (B1, B6, B12) by zero-crossing derivative spectrophotometry - Özgür, MÜ; Koyuncu, I (Tubitak Scientific & Technological Research Council Turkey, 2002)
A new method for determining ternary mixtures of vitamin B-1, B-6 and B-12 using second derivative spectrophotometry is described. The procedure is accurate, nondestructive and does not require any separation step or the solving of equations. Calibration graphs were linear up to 20 mugml(-1) of vitamin B-1 at 228.9 nm (r=0.9999), vitamin B-6 at 309.6 nm (r=0.9999) and vitamin B-12 at 361.7 nm (r=0.9998). The method was successfully applied fur analyzing synthetic mixtures and commercial pharmaceutical preparations.
Keywords: derivative spectrophotometry; vitamins; B-1; B-6; B-12; PERFORMANCE LIQUID-CHROMATOGRAPHY; WATER-SOLUBLE VITAMINS; Chemistry; Engineering